Perancangan Alat Bantu Praktik Arm Robot pada Penggunaan Teaching Pendant dengan pendekatan Value Engineering - M Yani Syafei; Clara Eunike Wahyuningsih (President University, 2019)
Controlling robot use a Teaching Pendant to communicate between users and arm robot. Teaching Pendant has a weight of about 1,250 kg. Left hand is used to handle teh Teaching Pendant and the on/off of motor o the arm robot. And the right hand is used as an operator in pressing the drive button in the Teaching Pendant. The position of users is stand when practicing controlling robot. The user feels some of the pain in the left hand, right hand and waist when using the Teaching Pendant. Based on the problem, I propose for tool to hold the Teaching Pendant. The method that use is the Value Engineering approach, making FAST diagrams for determining the function of the tools, and Nordic Body map to obtain the real data of pain. Respondent are users of Teaching Pendant. The result was 67,98% feel the pain because using the Teaching Pendant. The function of the tool that has been made is to hold the Teaching Pendant, using hollow iron for the materials. Tool testing was carried out with the same respondents, and they must fill the Nordic Body Map after they used the tool. The result of using this tool are able to reduce the total pain by 36,36% from the total pain in the beginning.